TINJAUAN KINERJA SHELTER PADA BRT KORIDOR 2 (UNGARAN – TERBOYO) - Untara Untara; Yanuar Christyawan; Supriyono Supriyono; Tanto Djoko Santoso (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Shelter of BRT Semarang is a facility that specifically designed as a stopping Bus Rapid Transit in accordance with the Decision of the Director General of Land Transportation N0: 271/HK.105/DRJD/96 and APTA Standard 2010, as the local Government's efforts to provide public transportation. Based on the background then performed research BRT shelter performance. Descriptive method is applied to explain the performance of BRT shelter. The results along the BRT route Ungaran - Terboyo showed some shelter that are less the standard, such as the shelter is too small dimensions, the distance between the shelter that do not fit, and there is support land/resurrection is not accommodated by the shelter of BRT. Even a few passengers ever climbed/descended outside the shelter. Therefore, from the existing 63 shelters needed some advice, first required the construction of 16 new shelter location points so that the users who have not been able to reach the shelter can be accommodated; need to increase 3 shelter, 1 shelter need to renovation and removal of 2 shelter that is not optimal; the second need to be given direction for users shelters BRT not to use an emergency exit to descend and climbed into bus.